Motor Ability and Mental Health of Young Children: A Longitudinal Study - Hirata, Shogo; Kita, Yosuke; Suzuki, Kota; Kitamura, Yuzuki; Okuzumi, Hideyuki; Kokubun, Mitsuru (Frontiers in Education, 2021)
This study used a longitudinal method to investigate relations between motor abilities and mental health in young children. We analyzed longitudinal data of 38 Japanese children who were 3–6 years old. We administered the Movement Assessment Battery for Children – Second edition (MABC2) and Strength and Difficulties Questionnaire (SDQ) at 3–4 years and 5–6 years of age: MABC2 was used to evaluate each child's motor ability; SDQ was used to assess the degree of their mental health difficulties and prosocial behavior. Logistic regression results indicated that the MABC2 score at 3–4 years can predict the risk of motor skill impairments at 5–6 years (adjusted odds ratio was .354). Motor ability assessed at 3–4 years, however, did not predict the risk of mental health problems at 5–6 years. Mental health problems that occurred at 5–6 years were related only to individual SDQ score differences at 3–4 years. Analyses of longitudinal quantitative changes in motor ability and mental health confirmed these results. The MABC2 total score at 3–4 years was not related to later prosocial behavior. Boys tended to obtain a lower MABC2 score at 5–6 years. Girls tended to obtain a higher SDQ prosocial score at 5–6 years. Results of this study suggest that motor skill impairment and SDQ-measured mental health are independent characteristics in young Japanese children aged 3–6 years.